Enhancing Student Engagement and Learning Outcomes through the Implementation of the TPS (Think Pair Share) Cooperative Learning Model - Rahmawati, Helmi; Haeriah, Haeriah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The issue of low activity and poor learning outcomes in mathematics among high school students is still prevalent. This research aims to enhance the activity and learning outcomes of 10th-grade students at MA Darul Mahmudien NW Montonggamang by implementing the Think Pair Share (TPS) cooperative learning model, specifically in the topic of linear equations and inequalities with a single variable absolute value. A classroom action research was conducted over 3 cycles, involving 26 students as research subjects. Student learning outcome data was collected through evaluation tests, while student and teacher activities were recorded using observation sheets. Descriptive analysis was applied, including the calculation of learning mastery equations and student mathematics learning outcomes. The research findings indicate a progressive increase in student activity scores across the 3 cycles. In Cycle I, the average student activity score was 12.65, categorized as moderate; in Cycle II, it rose to 16.25, categorized as high; and in Cycle III, the score reached 19.33, indicating a very high level of activity. The improvement in learning mastery was evident within each cycle. The average student scores were as follows: Cycle I - 57.8 with a learning mastery rate of 68.97%, Cycle II - 64.60 with a learning mastery rate of 81.82%, and Cycle III - 74.17 with a learning mastery rate of 86.96%. Based on these research outcomes, it can be concluded that the implementation of the Think Pair Share cooperative learning model effectively enhances both the activity and mathematics learning outcomes of 10th-grade students at MA Darul Mahmudien NW Montonggamang in the subject of linear equations and inequalities with a single variable absolute value.